2021
DOI: 10.9734/jpri/2021/v33i60b34864
|View full text |Cite
|
Sign up to set email alerts
|

Role of Medicinal Plants in the Management of Diabetes Mellitus: A Review

Abstract: Diabetes mellitus is a worse metabolic condition in which level of glucose and lipid increased in blood circulation due to insufficient insulin functionality that may lead to worse the complication like atherosclerosis, dyslipidemia, gangrene, limb amputation, kidney failure, and many more. Furthermore, high concentration of glucose in blood stream can directly produce reactive oxygen species which ultimately more worsen the conditions like dyslipidemia, atherosclerosis etc. This disorder is expected to affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Plant chemicals can be classified into several broad groups: alkaloids, aromatic acids, carotenoids, coumarins, essential oils, flavonoids, glycosides, organic acids, phenols and phenolics, phytosterols, saponins, steroids, tannins, terpenes, and terpenoids. Vitamins and medicinal plants have recently been found to have anti-diabetic, anti-hyperglycemic, anti-lipidemic, hypoglycemic, and insulin-mimicking effects in pharmacological trials [19], [20]. Moringa oleifera is one plant that has the potential to treat diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Plant chemicals can be classified into several broad groups: alkaloids, aromatic acids, carotenoids, coumarins, essential oils, flavonoids, glycosides, organic acids, phenols and phenolics, phytosterols, saponins, steroids, tannins, terpenes, and terpenoids. Vitamins and medicinal plants have recently been found to have anti-diabetic, anti-hyperglycemic, anti-lipidemic, hypoglycemic, and insulin-mimicking effects in pharmacological trials [19], [20]. Moringa oleifera is one plant that has the potential to treat diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The major groups of phytochemicals are alkaloids, aromatic acids, carotenoids, coumarins, essential oils, flavonoids, glycosides, organic acid, phenols and phenolics, phytosterols, protease inhibitors, saponins, steroids, tannins, terpenes, and terpenoids [21][22][23]. Recent pharmacological studies have revealed the anti-diabetic properties of medicinal plants and vitamins including anti-hyperglycemic, anti-lipidemic, hypoglycemic, and insulin mimicking [24,25]. The treatment strategies for DM have improved over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…The antidiabetic phytochemicals have been identified based on the differences in their chemical structures [18], [19]. Some of the major classes of phytochemicals are Alkaloids, aromatic acids, carotenoids, coumarins, essential oils, flavonoids, glycosides, organic acids, phenols and phenolics, phytosterols, protease inhibitors, saponins, steroids, tannins, terpenes, and terpenoids [20]- [24].…”
Section: Introductionmentioning
confidence: 99%